Advanced gas turbine cooling: double-wall turbine cooling technologies in turbine NGV/blade applications - Murray, AV (2019)
The drive to increase the thermal efficiency and specific power output of the gas turbine results in increasing turbine temperatures which necessitate active cooling of the turbine blades. High performance cooling systems are required which achieve the necessary blade life requirements whilst minimising coolant consumption. This thesis explores one potential turbine cooling system advancement termed the double-wall, effusion cooled system which is envisaged to find application in areas where high cooling performance is required. Single wall effusion cooling performance is initially investigated given its importance in the double-wall system. An experimental investigation is performed and used to validate a computational model. A two-dimensional superposition method for predicting effusion cooling performance is presented and validated based upon the experimental and computational data. The superposition method was used as part of a computationally light, decoupled conjugate method which was developed to predict the cooling performance of double-wall geometries. This decoupled method was used to assess several developed double-wall geometries. Those geometries which exhibited preferable cooling characteristic were manufactured for testing in a novel experimental facility, designed and commissioned as part of the thesis work. The facility incorporates several features to improve the quality of data obtained and matches several relevant non-dimensional parameters. The facility was used to obtain both overall effectiveness and film effectiveness results for five flat plate, double-wall geometries. This data was then used to infer the convective cooling performance of each geometry at varying coolant flow rates, with preferable cooling features identified. The results indicate the high cooling performance achieved in double-wall, effusion cooled geometries. Two computational methods were used to replicate the experimental setup utilising boundary conditions obtained from the facility. The first was a fully conjugate solver, and the second was a modified form of the developed decoupled method. The results from both sets of simulations compared favourably with the experimental data. The decoupled conjugate method was particularly encouraging given the vast reduction in simulation time required when compared to the fully conjugate solver. Thermomechanical analyses were performed to identify how various geometric features influence the stress field developed under thermal load, which has direct implication on blade lifespan. The work was successful in indicating certain double-wall configurations which could reduce the magnitude of the stresses.